161k views
4 votes
29: If kn≠ k , and n = 1/k , which of the following expression is equivalent to (1-k)/(1-n)A. -n B. -k C. 1D. k

29: If kn≠ k , and n = 1/k , which of the following expression is equivalent to (1-k-example-1
User CPerson
by
4.9k points

1 Answer

2 votes

The expression if given as,


(1-k)/(1-n)

The condition is given as,


n=(1)/(k)

Substitute this value in the expression,


=(1-k)/(1-(1)/(k))

Resolve the rational expression as,


\begin{gathered} =(1-k)/(((k-1)/(k))) \\ =(k(1-k))/(k-1) \\ =(-k(k-1))/(k-1) \end{gathered}

Cancelling out the common factor,


\begin{gathered} =(-k(1))/((1)) \\ =-k \end{gathered}

Thus, the simplified form of the given expression is obtained as,


-k

Therefore, option B is the correct choice.

User Bigmeister
by
5.5k points